Urinary tract infection and bladder catheterism: prophylactic and laboratorial aspects - Kluczynik, Caroline Evelin Nascimento; Solano, Gabriela Beserra; Lima, Martha Priscila Dantas de; Catão, Raïssa Mayer Ramalho (Revista de Enfermagem UFPE on line, 2008)
ABSTRACT Objective: to check the prevalence of microorganisms isolated and described some procedures needed for prevention and diagnosis of urinary tract infections (UTI) when associated with bladder catheterization. Method: this is about a bibliographic study whose sources correspond to articles, books and manuals related to the theme. Results: the most prevalent organisms were Escherichia coli, Klebsiella sp. and Enterobacter sp. Conclusions: given the foregoing, it’s observed that the evaluation of these patients should be continuous, on suspicion of UTI the laboratorial exams should be prescribed and the samples should be collected by competent professional to facilitate and make more precise plan for the treatment of patients with this type of infection. Descriptors: infection; urinary tract; catheter; tests; laboratorial research. RESUMO Objetivos: verificar a prevalência dos microrganismos isolados e descrever alguns procedimentos necessários para prevenção e diagnóstico da infecção do trato urinário (ITU) quando associados ao cateterismo vesical. Métodos: este estudo tem cunho bibliográfico, suas fontes correspondem aos artigos, livros e manuais pertinentes ao tema. Resultados: os microrganismos mais prevalentes foram Escherichia coli, Klebsiella sp. e Enterobacter sp. Conclusão: diante do exposto, observa-se que a avaliação destes pacientes deve ser contínua, em suspeita de ITU os exames laboratoriais devem ser prescritos e as amostras devem ser coletadas por profissional competente, a fim de facilitar e tornar mais precisa o plano de tratamento do paciente com este tipo de infecção. Descritores: infecção; trato urinário; cateter; exames; investigação laboratorial. RESUMEN <span style="font-family: ";Trebuchet MS";,";sans-serif";; font-size: 9pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: ES-AR; mso-bidi-font-family: Arial; mso-fareast-language: PT-BR;" lang="ES-AR">Objetivo<span style="font-family: ";Trebuchet MS";,";sans-serif";; font-size: 9pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: ES-AR; mso-bidi-font-family: Arial; mso-fareast-language: PT-BR;" lang="ES-AR">: verificar la prevalencia de los microorganismos aislados y describir algunos de los procedimientos necesarios para la prevención y diagnóstico en la i<span style="font-family: ";Trebuchet MS";,";sans-serif";; font-size: 9pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: ES-AR; mso-bidi-font-family: Arial; mso-fareast-language: PT-BR;" lang="ES-AR">nfecciones del aparato urinario (IAU) cuando se asocian con el cateterismo vesical. Métodos: El estudio fue de naturaleza bibliográfica, a partir de artículos científicos, libros y manuales pertinentes al tema. Resultados: los organismos más prevalentes fueron Escherichia coli, Klebsiella sp. y Enterobacter sp. <span style="font-family: ";Trebuchet MS";,";sans-serif";; font-size: 9pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: ES-AR; mso-bidi-font-family: Arial; mso-fareast-language: PT-BR;" lang="ES-AR">Conclusiones<span style="font-family: ";Trebuchet MS";,";sans-serif";; font-size: 9pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: ES-AR; mso-bidi-font-family: Arial; mso-fareast-language: PT-BR;" lang="ES-AR">: Se observa que la avaluación de esos pacientes debe ser continua en los casos que se sospeche de infecciones urinarias, con prescripción de exámenes de laboratorio, destacándose que las muestras deben ser colectadas por profesionales competentes, para que el plano de tratamiento del paciente sea precisa. Descriptores: infección; aparato urinario; catéter; investigación laboratorial.